Exploring the Influence of Parental Involvement on Stress Coping Mechanisms among Students in Tamansari, Lelea, Indramayu, Indonesia: A Correlational Analysis - Maria Ivana Putri; Agoes Dariyo, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
Various challenges experienced by a person in adolescence can make him feel stressed. Therefore, knowing the proper response and how to cope with stress is essential. Parental involvement is crucial in directing children to have good coping. This study aims to determine the relationship between father involvement and active and internal coping stress in students in Indramayu. This research is in the form of a quantitative correlational method by distributing questionnaires in schools located in Tamansari, Lelea, Indramayu, West Java, Indonesia. The variable perception of father involvement is measured by Reported Father Involvement Scale (Finley & Schwartz, 2004) and Coping stress is measured by the Coping Across Situation Questionnaire (Seiffge-Krenke, 1990). The participants in this research were 410 adolescents, ranging from adolescents aged 11-19 years. Using the Spearman correlation test, the data analysis technique using with the SPSS version 22 program. The result showed a positive and significant relationship between father involvement and active coping stress (r = 0,400 and p= 0,000) and internal coping stress (r = 0,385 and p = 0,000). These results indicatethat the higher the father's involvement, the higher the level of active and internal coping in adolescents in Tamansari, Lelea, Indramayu.